Etching composition and application thereof

By using an etching composition containing water, organic solvent, surfactant and acid, the problem of cobalt layer thickness control and insufficient material compatibility is solved, and the adjustable cobalt etching rate and good compatibility of various materials are achieved.

CN119913513APending Publication Date: 2025-05-02ANJI MICROELECTRONICS TECH (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311375008.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the thickness of the cobalt layer, and its compatibility with other materials is insufficient, affecting the performance of components.

Method used

An etching composition including water, organic solvent, surfactant and acid is used to control the etching rate of cobalt by adjusting the proportion of the composition, and improve compatibility with materials such as TiN, Ti, SiO2, SiN, etc.

Benefits of technology

Controllable etching of the thickness of the cobalt layer is achieved, compatibility with other materials is improved, and the process operation window is expanded to meet different production needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004507689830000031
    Figure BDA0004507689830000031
  • Figure BDA0004507689830000043
    Figure BDA0004507689830000043
  • Figure BDA0004507689830000051
    Figure BDA0004507689830000051
Patent Text Reader

Abstract

The invention provides an etching composition. The etching composition comprises water, an organic solvent, a surfactant and an acid. After the technical scheme is adopted, adjustable etching of Co can be realized, and the etching rate can be adjusted so as to meet different production requirements; meanwhile, the material has good compatibility with TiN, Ti, SiO2, SiN and other materials, the technological operation window is large, and the wide application prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of etching, and in particular to an etching composition and application thereof. Background Art

[0002] With the continuous advancement of semiconductor technology, more and more metal materials are being applied to semiconductor structures, especially cobalt and cobalt alloy materials. Cobalt has excellent electrical conductivity, high temperature thermal stability and excellent mechanical properties, so cobalt materials have become more and more common in some advanced manufacturing. In some components, the thickness of the cobalt layer has a great influence on the performance of the components, so it is necessary to strictly control the thickness of the cobalt layer. Therefore, there is a need in the art for a cobalt etching solution that can control the etching rate of cobalt, so as to achieve the purpose of controlling the thickness of the cobalt layer, and at the same time has good compatibility with other materials (Ti, TiN, Oxide, SiN, etc.). Summary of the invention

[0003] The object of the present invention is to provide an etching composition that can adjust the etching rate of cobalt and has good compatibility with materials such as TiN, Ti, SiO2, SiN, etc. Specifically, the etching composition of the present invention includes water, an organic solvent, a surfactant and an acid.

[0004] Preferably, the organic solvent is an organic alcohol with C < 6;

[0005] The mass percentage content of the organic solvent is 0.1-50%.

[0006] Preferably, the organic solvent is selected from one or more of methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, 2-pentanol, 3-pentanol, n-hexanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, etc.;

[0007] The mass percentage content of the organic solvent is 3% to 30%.

[0008] Preferably, the surfactant is selected from one or more of ethylene glycol monobutyl ether, ethylene glycol glycidyl ether, poly(ethylene glycol-propylene glycol) monobutyl ether, diethylene glycol dimethyl ether, propylene glycol phenyl ether, propylene glycol methyl ether, dodecylamine polyoxyethylene ether, polyethylene glycol, polyethylene glycol-propylene glycol copolymer, vinyl pyrrolidone-vinyl acetate copolymer, SUPERWET-320, SUPERWET-340, SUPERWET-360, SURFYNOL420, SURFYNOL440, coconut fatty acid diethanolamide, dodecyltrimethylammonium chloride, benzyldodecyldimethylammonium chloride, myristyltrimethylammonium chloride, benzalkonium chloride, hexadecyltrimethylammonium bromide, and tetraheptylammonium bromide.

[0009] Preferably, the mass percentage content of the surfactant is 0.001% to 10%.

[0010] Preferably, the surfactant has a mass percentage content of 0.01% to 5%.

[0011] Preferably, the acid is selected from an organic acid or an inorganic acid, and the organic acid is selected from one or more of a polycarboxylic acid, a mono / polyamino polycarboxylic acid, and a mono / polyhydroxy polycarboxylic acid;

[0012] The inorganic acid is selected from one or more of sulfuric acid, hydrochloric acid, perchloric acid, nitric acid, hydrofluoric acid, hydrobromic acid, periodic acid, and phosphoric acid.

[0013] Preferably, the polycarboxylic acid is selected from one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, methylsuccinic acid, adipic acid, 2-methylglutaric acid, 3-methylglutaric acid, phthalic acid, terephthalic acid, trimesic acid, trimesic acid, and 1,2,3,4-butanetetracarboxylic acid;

[0014] The mono / polyamino polycarboxylic acid is selected from one or more of nitrilotriacetic acid, iminodiacetic acid, diethylenetriaminepentaacetic acid, ethylenediaminetetraacetic acid, ethylenediaminediacetic acid, oxalic acid dipropionic acid, cyclohexanediaminetetraacetic acid, triethylenetetraaminehexaacetic acid, and hydroxyethylethylenediaminotriacetic acid;

[0015] The mono / polyhydroxy polycarboxylic acid is selected from one or more of tartaric acid, malic acid, citric acid, 2-hydroxymalonic acid, 2-hydroxyglutaric acid, 3-hydroxyglutaric acid, 2-hydroxyadipic acid, and glucaric acid.

[0016] Preferably, the mass percentage content of the acid is 0.001% to 35%.

[0017] The invention also discloses a use of any of the above etching compositions for etching cobalt materials.

[0018] Compared with the prior art, the above technical solution has the following beneficial effects:

[0019] 1. Adjustable etching of Co can be achieved, so that its etching rate can be adjusted to meet different production needs.

[0020] 2. It has good compatibility with materials such as TiN, Ti, SiO2, SiN, etc., and has a large process operation window and broad application prospects. DETAILED DESCRIPTION

[0021] The advantages of the present invention are further described below in conjunction with specific embodiments.

[0022] The components and contents of the examples listed in Table 1 were proportioned, and the corresponding etching compositions were prepared after the corresponding components were fully stirred and mixed.

[0023] Table 1 Components and contents of etching compositions in Examples 1-10 and Comparative Example 1

[0024]

[0025] The units of the contents in the above table are all mass percentages.

[0026] In order to investigate the etching rate of the composition on various materials, the etching rates of metal TiN, metal Co, metal Ti, non-metal oxide, and SiN were tested respectively. The metal etching rate test method is as follows: Co, Ti, and TiN blank wafers are selected, sliced ​​into 5*5cm size, and placed in a single-wafer rotary cleaning machine for treatment. The treatment time range is 1-10min, preferably 5min, the rotation speed setting range is 200-900rpm, preferably 600rpm, and the test temperature is 25-70℃, preferably 50℃. After the treatment, the blank wafers are taken out, rinsed, and blown dry with high-purity nitrogen.

[0027] The corrosion rate test method is as follows:

[0028] 1) Use a metal film thickness gauge to test the resistance (R1) of a 5*5cm metal blank wafer to be tested;

[0029] 2) placing the 5*5 cm metal blank wafer to be tested in a single wafer spin cleaning machine;

[0030] 3) Take out the 5*5cm metal blank wafer, wash it with deionized water, blow dry it with high-purity nitrogen, and then use a metal film thickness gauge to test the resistance (R2) of the metal blank wafer;

[0031] 4) By inputting the above resistance value change and processing time into a suitable program, the etching rate can be calculated. The calculation formula is as follows:

[0032] ER=K(R2-R1) / T

[0033] Among them, R1 and R2 are the resistance values ​​of the metal blank wafer; T is the processing time of the microcontroller; K value is the coefficient, and the K value of different metal materials is different. The unit of metal corrosion rate is

[0034] The corrosion rate test method of non-metallic corrosion materials (SiN, Oxide) is as follows:

[0035] 1) Using an ellipsometer to measure the first thickness D1 of the non-metal material layer (AlN) of a 5*5cm non-metal blank wafer to be tested;

[0036] 2) placing the 5*5 cm non-metallic blank wafer to be tested in a single-wafer spin cleaning machine for 1 to 10 minutes, with the rotation speed set at 200 to 900 rpm;

[0037] 3) taking out the blank wafer, washing it with deionized water, drying it with high-purity nitrogen gas, and then measuring the second thickness D2 with an ellipsometer;

[0038] 4) By inputting the above thickness changes and processing time into a suitable program, the corrosion rate can be calculated. The calculation formula is as follows:

[0039] ER=(D1-D2) / T

[0040] Wherein, D1 and D2 are the first thickness and the second thickness of the non-metal blank wafer respectively; T is the processing time. The test data is shown in Table 2. The units of etching rate in Table 2 are

[0041] Table 2 Etching rate test results of Examples 1-10 and Comparative Example 1

[0042]

[0043]

[0044] It can be seen from the results in Table 2 that the etching compositions in Examples 1-12 have a higher etching rate for cobalt at different temperatures (25-70°C), rotation speeds (200-900rpm) and operating times (1-10min), but have lower etching rates for TiN, Ti, silicon oxide, and SiN, and have better compatibility; and the operating window is larger, which can adapt to different production conditions. It can be seen from the results of Comparative Example 1 that after no acid is added, the etching rate of Co is lower, indicating that the acid etching system in the present invention is beneficial to improve the etching rate of cobalt. It can be seen from Comparative Example 2 that when the amount of acid added is too little, the Co etching rate is still low. It can be seen from Comparative Example 3 that when the amount of acid added is too high, the Co etching rate is higher, and the TiN and Ti etching rates also increase significantly.

[0045] In order to further investigate the adjustability of the etching composition of the present invention for the cobalt etching rate, a group of etching compositions was further prepared, including: deionized water, the content is 64.99%, ethylene glycol monobutyl ether, the content is 5%, oxalic acid, the content is 0.01%, and ethylene glycol, the content is 30%. The etching composition was further mixed with deionized water to obtain etching compositions with different ratios, as shown in Table 3.

[0046] Table 3 Relative proportions of water content and etching composition in Examples 11-16 and Comparative Example 4

[0047] Example Water content Etching composition 13 10.0 90.0 14 25.0 75.0 15 50.0 50.0 16 75.0 25.0 17 90.0 10.0 18 99.0 1.0 Comparative Example 4 100.0 0.0

[0048] The present invention adopts the following technical means: testing the etching rates of metals Co, Ti, TiN, non-metallic oxide, SiN, wherein the metal etching rate testing method is as follows: Co, TiN, Ti blank wafers are selected, the blank wafers are sliced ​​into 5*5cm size, and placed in a single-wafer rotary cleaning machine for processing, the processing time range is 1-10min, 3min is selected this time, the speed setting range is 200-900rpm, 600rpm is selected this time, the testing temperature is 25-70℃, 40℃ is selected this time, and after processing, the blank wafers are taken out, rinsed, and blown dry with high-purity nitrogen.

[0049] The corrosion rate test method is as follows:

[0050] 1) Use a metal film thickness gauge to test the resistance (R1) of a 5*5cm metal blank wafer to be tested;

[0051] 2) placing the 5*5 cm metal blank wafer to be tested in a single wafer spin cleaning machine;

[0052] 3) Take out the 5*5cm metal blank wafer, wash it with deionized water, blow dry it with high-purity nitrogen, and then use a metal film thickness gauge to test the resistance (R2) of the metal blank wafer;

[0053] 4) By inputting the above resistance value change and processing time into a suitable program, the etching rate can be calculated. The calculation formula is as follows:

[0054] ER=K(R2-R1) / T

[0055] Among them, R1 and R2 are the resistance values ​​of the metal blank wafer; T is the processing time of the microcontroller; K value is the coefficient, and the K value of different metal materials is different. The unit of metal corrosion rate is

[0056] The corrosion rate test method of non-metallic corrosion materials (SiN, Oxide) is as follows:

[0057] 1) Using an ellipsometer to measure the first thickness D1 of the non-metal material layer (AlN) of a 5*5cm non-metal blank wafer to be tested;

[0058] 2) Place the 5*5 cm non-metallic blank wafer to be tested in a single-wafer spin cleaning machine for 3 minutes, with the rotation speed set at 600 rpm;

[0059] 3) taking out the blank wafer, washing it with deionized water, drying it with high-purity nitrogen gas, and then measuring the second thickness D2 with an ellipsometer;

[0060] 4) By inputting the above thickness changes and processing time into a suitable program, the corrosion rate can be calculated. The calculation formula is as follows:

[0061] ER=(D1-D2) / T

[0062] Where D1 and D2 are the first thickness and the second thickness of the non-metal blank wafer respectively; T is the processing time. The test results are shown in Table 4. The unit of etching rate is

[0063] Table 4 Blank wafer etching rates of Examples 13-18 and Comparative Example 4

[0064]

[0065]

[0066] As can be seen from Table 4, as the etching composition and the water dilution ratio are different, the cobalt etching rate can be adjusted, the higher the dilution ratio of the etching composition / water, the greater the cobalt etching rate, the lower the dilution ratio of the etching composition / water, the lower the cobalt etching rate. The etching rates of other materials except cobalt are all relatively low, showing that the composition has good compatibility with it. Pure water (comparison 2) has a certain etching rate for cobalt, but the etching rate is not as good as the etching composition.

[0067] Based on the above embodiments and their test results, it can be seen that the etching composition in the present invention can adjust the etching rate of cobalt by diluting it in different proportions, and at the same time has good compatibility with materials such as TiN, Ti, SiO2, SiN, etc., and has a low etching rate for various materials, which meets actual production needs and has broad application prospects.

[0068] It should be noted that the embodiments of the present invention have better practicability and do not impose any form of limitation on the present invention. Any technician familiar with the field may use the technical content disclosed above to change or modify it into an equivalent effective embodiment. However, any modification or equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An etching composition, characterized in that Including water, organic solvents, surfactants and acids.

2. The etching composition according to claim 1, characterized in that The organic solvent is an organic alcohol with a C value less than 6; The mass percentage content of the organic solvent is 0.1-50%.

3. The etching composition according to claim 2, characterized in that The organic solvent is selected from one or more of methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, 2-pentanol, 3-pentanol, n-hexanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, etc.; The mass percentage content of the organic solvent is 3% to 30%.

4. The etching composition according to claim 1, characterized in that The surfactant is selected from one or more of ethylene glycol monobutyl ether, ethylene glycol glycidyl ether, poly(ethylene glycol-propylene glycol) monobutyl ether, diethylene glycol dimethyl ether, propylene glycol phenyl ether, propylene glycol methyl ether, dodecylamine polyoxyethylene ether, polyethylene glycol, polyethylene glycol-propylene glycol copolymer, vinyl pyrrolidone-vinyl acetate copolymer, SUPERWET-320, SUPERWET-340, SUPERWET-360, SURFYNOL420, SURFYNOL440, coconut fatty acid diethanolamide, dodecyltrimethylammonium chloride, benzyldodecyldimethylammonium chloride, myristyltrimethylammonium chloride, benzalkonium chloride, hexadecyltrimethylammonium bromide, and tetraheptylammonium bromide.

5. The etching composition according to claim 1, characterized in that The mass percentage content of the surfactant is 0.001% to 10%.

6. The etching composition according to claim 5, characterized in that The surfactant preferably has a mass percentage content of 0.01% to 5%.

7. The etching composition according to claim 1, characterized in that The acid is selected from an organic acid or an inorganic acid, and the organic acid is selected from one or more of a polycarboxylic acid, a mono / polyamino polycarboxylic acid, and a mono / polyhydroxy polycarboxylic acid; The inorganic acid is selected from one or more of sulfuric acid, hydrochloric acid, perchloric acid, nitric acid, hydrofluoric acid, hydrobromic acid, periodic acid, and phosphoric acid.

8. The etching composition according to claim 7, characterized in that The polycarboxylic acid is selected from one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, methylsuccinic acid, adipic acid, 2-methylglutaric acid, 3-methylglutaric acid, phthalic acid, terephthalic acid, trimesic acid, trimesic acid, and 1,2,3,4-butanetetracarboxylic acid; The mono / polyamino polycarboxylic acid is selected from one or more of nitrilotriacetic acid, iminodiacetic acid, diethylenetriaminepentaacetic acid, ethylenediaminetetraacetic acid, ethylenediaminediacetic acid, oxalic acid dipropionic acid, cyclohexanediaminetetraacetic acid, triethylenetetraaminehexaacetic acid, and hydroxyethylethylenediaminotriacetic acid; The mono / polyhydroxy polycarboxylic acid is selected from one or more of tartaric acid, malic acid, citric acid, 2-hydroxymalonic acid, 2-hydroxyglutaric acid, 3-hydroxyglutaric acid, 2-hydroxyadipic acid, and glucaric acid.

9. The etching composition according to claim 1, wherein The mass percentage content of the acid is 0.001% to 35%.

10. Use of the etching composition according to any one of claims 1 to 9 for etching cobalt materials.